Perturbations of the flow induced by a microcapsule in a capillary tube. (17th March 2017) - Gubspun, J; Loubens, C de; Trozzo, R; Deschamps, J; Georgelin, M; Edwards-Levy, F; Leonetti, M
Abstract: Soft microcapsules moving in a cylindrical capillary deform from quasi-spherical shapes to elongated shapes with an inversion of curvature at the rear. We investigated the perturbation of the flow by particle tracking velocimetry around deformed microcapsules in confined flow. These experiments are completed by numerical simulations. Microcapsules are made of a thin membrane of polymerized human albumin and their shear elastic moduli are previously characterized in a cross flow chamber. Firstly, the velocity of the microcapsule can be calculated by theoretical predictions for rigid spheres, even for large deformations as 'parachute-like' shapes, if a relevant definition of the ratio of confinement is chosen. Secondly, at the rear and the front of the microcapsule, the existence of multiple recirculation regions is governed by the local curvature of the membrane. The amplitudes of these perturbations increase with the microcapsule deformation, whereas their axial extents are comparable to the radius of the capillary whatever the confinement and the capillary number. We conclude that whereas the motion of microcapsules in confined flow has quantitative similitudes with rigid spheres in terms of velocity and axial extent of the perturbation, their presence induces variations in the flow field that are related to the local deformation of the membrane as in droplets.